The Influence Of Leadership Style, Organizational Culture, And Work Motivation On Employee Performance - Zeanette T Lisbet; Wulandari; Yeny Rokhilawati; Anita Kusuma Dewi (Journal Management & Economics Review (JUMPER), 2026)
The purpose of this study is to evaluate the impact of leadership style, organizational culture, and motivation on employee performance. Employee performance has become one of the most significant determinants of organizational success in today’s highly competitive business environment. Therefore, organizations need to understand the variables that impact performance. This research will adopt the quantitative method of research with an explanatory research design in order to determine the cause-and-effect relationship among the variables. Information gathering was done using a questionnaire administered to the employees using the Likert Scale. Analysis of data was done through the use of descriptive statistics and multiple regression analyses with the aid of classical assumptions, namely, tests for normality, multicollinearity, and heteroscedasticity. Findings from the study show that leadership style, organizational culture, and work motivation positively affect the performance of employees. Moreover, the findings also reveal that together, these three factors significantly affect employee performance. The R2 value indicates that a high percentage of employee performance is determined by the three variables mentioned above. From the results, one can infer that leadership, organizational culture, and motivation are key elements in improving employee productivity. In light of this, organizations should develop an adaptive form of leadership, create a supportive organizational culture, and introduce motivational programs to boost employee motivation. This research adds to the body of knowledge concerning the effect of these variables on organizational performance.